The Response of Reciprocal Teaching as the Solution for an English Readers - Udin, Imran Trista (International Journal of English Language and Pedagogy, 2023)
To find out whether or not the students are interested in joining the reading class through Reciprocal reading. This research employed Quasi Experimental design. The sample consisted of 68 students of class X 1 and II at SMA Negeri 4 Makassar. The data were collected through questionnaire for students’ interest. Data on the students’ interest were analyzed using Likert scale. The results of the research is the use of Reciprocal reading increased the students’ interest in joining the reading class. It can be concluded that the use of Reciprocal reading is effective to be implemented in improving the students’ reading skills and the students have high interest and active toward teaching reading through Reciprocal reading.